2021
DOI: 10.21203/rs.3.rs-151144/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unraveling the neuroprotective effect of Tinospora cordifolia in Parkinsonian mouse model through proteomics Approach.

Abstract: Stress-induced dopaminergic (DAergic) neuronal death in the midbrain region is the primary cause of Parkinson’s disease (PD). From the discovery of L-dopa, multiple drugs were discovered to improve lifestyle of PD patients, but they failed due to their multiple side effects. Tinospora cordifolia (Tc), a medicinal herb has been used in traditional medicines to treat neurodegenerative diseases. In our previous study, the neuroprotective role of Tc against MPTP intoxicated Parkinsonian mice was reported. Here, we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Flavonoids as Neuroprotective Agents. Flavonoids exert a multiplicity of neuroprotective effects against neurodegenerative diseases to suppress neuroinflammation and to improve cognitive function (Figure 3) [87][88][89]. Recently, one study from Gu et al showed antiamyloid property of the flavonoid prepared from the caper leaf and fruit [90].…”
Section: Role Of Flavonoids In Neuroprotectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids as Neuroprotective Agents. Flavonoids exert a multiplicity of neuroprotective effects against neurodegenerative diseases to suppress neuroinflammation and to improve cognitive function (Figure 3) [87][88][89]. Recently, one study from Gu et al showed antiamyloid property of the flavonoid prepared from the caper leaf and fruit [90].…”
Section: Role Of Flavonoids In Neuroprotectionmentioning
confidence: 99%
“…Flavonoids play a crucial role in preventing the adverse effect of ROS by protecting the neurons against oxidative stress and hence suppress neuronal damage and improve cognitive function [20] [123]. Besides flavonoids, its derivatives have been reported to have potential antioxidant and neuroprotective activity in vitro and in vivo [89,[124][125][126][127]. Various studies have suggested that flavonoids exert its action especially in neuroprotection against AD by affecting gene expression and interacting with mitochondria and the intracellular signalling modulation of cascades that control neuronal differentiation, survival, and death [73].…”
Section: Role Of Flavonoids In Neuroprotectionmentioning
confidence: 99%
“…The brains of paraoxon-treated mice contain high levels of thrombin, PAR1, and pERK, as well as enhanced electrical impulses in the CA1 and CA3 neurons of the hippocampal. A PAR1 antagonist is used to minimize excessive electrical activity [269][270][271][272][273][274][275]. These findings suggest that thrombin is implicated in an epileptic activity that is not triggered by trauma, raising new issues concerning the origins of thrombin in the CNS [276].…”
Section: In Central Nervous System Diseases the Neuro-glia Coagulonomementioning
confidence: 99%
“…In the last three decades, extensive research has provided proof of plethora of pharmacological properties of different parts of the plant (Figure 1). T. cordifolia is reported to have array of medicinal properties like-anti-diabetic (Stanely Mainzen Prince & Menon,2000Sonkamble & Kamble, 2015;Chacko, 2018;Khanal et al, 2019;Vora et al, 2020), anti-pyretic (Pendse et al, 1977;Ashok et al, 2010;Hussain et al, 2015;Rakib et al, 2020), hepato-protective (Bishayi et al, 2002;Panchabhai Therapeutics doi:10.31674/book.2021.tkwb et al, 2008Rakib et al, 2020), cardio-protective (Rao et al, 2005;Sharma et al, 2011a;Priya et al, 2017;Begum et al, 2021), neuro-protective (Kosaraju et al, 2014;Sharma & Kaur 2018;Birla et al, 2021), anti-allergic, anti-oxidant (Sharma & Joshi, 2011;Praveen et al, 2012;Prasad & Chauhan, 2019), anti-tumour (Jagetia, Nayak & Vidyasagar, 1998;Jagetia & Rao, 2006;Deepa et al, 2019;Palmieri et al, 2019), radio-protective (Goel et al, 2004;Sharma et al, 2011b;Patel et al, 2013) immuno-modulatory (Bishayi et al, 2002;Nageswari, Reddy & Venkatappa, 2018), anti-ulcer (Sarma et al, 1995;Bairy et al, 2002;Kaur, Singh & Kumar, 2014), anti-fertility…”
Section: Pharmacological Properties Of Tinospora Cordifoliamentioning
confidence: 99%
“…In the study, comparative analysis of different extraction processes was also evaluated, suggesting butanol extract to be the most potent in neuro-protective activity in comparison to hexane, chloroform, and ethyl acetate extracts following fractionation of the aqueous extract of Tinospora cordifolia (Sharma & Kaur, 2018). Birla et al, (2021) studied molecular mechanisms of the neuroprotective activity of the plant extract in a Rotenone intoxicated mouse model through a proteomics approach. The study demonstrated the therapeutic effect of the plant extract via regulation of multiple pathways, leading to the protection of dopaminergic neurons.…”
Section: Therapeuticsmentioning
confidence: 99%